The Wasps’ Nest: Antisemitism, Conspiracy Theory, and The Prioress’s Tale - Lampert, Lisa (Studies in the age of Chaucer, 2021)
Conspiracy theories are not only forms of explanation. They are narratives designed to evoke emotional response. This essay reads the thirteenth-century Anglo-Norman "Hugo de Lincolnia" and The Prioress’s Tale as conspiracy theory narratives, examining how they use language and imagery to generate aesthetic emotions, especially fear and disgust. I argue that a focus on the conspiracies represented in these texts reveals connections both to other contemporary narratives and to a long tradition of antisemitic narrative that extends through The Protocols of the Elders of Zion to the global conspiracy theories of the early twenty-first century.